Surface roughness as a quantitative approach to use-wear on macrolithic tools: A comparative analysis. (December 2022) - Delgado-Raack, Selina; Menasanch de Tobaruela, Jorge; Bettinardi, Italo; Soldevilla, José Antonio; Risch, Roberto
Highlights: Use-ware traces on macrolithic artefacts can be quantified through surface topography and roughness analyses. However, different measuring equipment and methods have been used in the past. The present study compares for the first time the roughness measurements obtained through different devices and techniques (photogrammetry, 3D scanning, and microscopy), taking into account the size and the petrographic particularities of the macrolithic tools. The results show that several devices (AutoScan-DS-EX, HP-3D-Scan and confocal microscopy) provide roughness values of artefact surfaces in the same order of magnitude and correctly detect height differences even in the range of 1–10 µm. We also determine that the use of different synthetic casts increases surface roughness measurements, confirming previous research. While confocal microscopy is the most reliable device, portable scanning devices, such as HP-3D-Scan Pro S3, are probably more suited for surface roughness analysis of large collections of macrolithic artifacts and do not require preparing synthetic replicas of the surfaces. Abstract: Use-wear analysis has been a well-established aspect of the study of artefact biography for decades, and it has recently developed along two different, though complementary methodological paths. While the classical or qualitative approach still relies largely on the experience gained from the combination of experimental tests, tribological principles and visual observation, new attempts try to define quantitative surface signatures. Surface topography and roughness analyses should allow one to associate surfaces to specific uses and warrant comparability and reproducibility of obtained datasets beyond textual descriptions and images. This approach is highly relevant to use-wear studies of macrolithic tools, where different techniques have made use of the available high-resolution devices. However, no systematic approach has been published yet with the aim of evaluating the operating capacity of the different systems and techniques. Consequently, the precision as well as the resolution of the data obtained and the comparability between results is questionable because of the complexity of the available technical options. The present study offers a method for surface roughness quantification of macrolithic tools and compares the results achieved with different 3D modeling devices.